Buyers pay for and sellers invest in a good reputation: More evidence from eBay - Przepiorka, W (2013)
This article contributes to the research on trust and reputation formation in anonymous online markets. I first give a formal account of the reputation mechanism in anonymous online markets and derive testable hypotheses. Based on the analysis of a large set of process data (N≈ 176,000), I corroborate a statistically and economically significant seller reputation effect on the probability of sale and the selling price both in auctions and fixed price offers. Moreover, my analysis shows that sellers making fixed price offers invest in a good reputation to a similar extent as buyers pay for it in auctions. Finally, I obtain repeated observations on a considerable subset of the buyer population by including highest non-winning bids in the analysis and show that buyers trade off sellers' reputations and prices within the set of offered items they choose to bid on. My findings provide further evidence that reputation systems solve trust problems and reduce transaction costs in anonymous online markets by providing incentives for traders' cooperative behavior. © 2012 Elsevier Inc.